A Judicialização da saúde: análise das consequências na gestão dos municípios de Belém e Ananindeua - CAVALCANTI, Leandro Calvoso (Universidade Federal do Pará, 2023)
The subject proposed to be addressed consists of a sad social reality, which must always be brought to the fore to enable it to be debated and ways to reduce the current illness seen in Brazilian public health be created. The constitutional norm guaranteeing health as a state duty is already 33 years old, since it was regulated by the 1988 Constitution, regulated by law 8080. The problem to be researched is verified when the judicialization of health, regarding the distribution of medication, reaches the Municipal Management, given that every time there is a judicial decision the Municipality is obliged to comply, otherwise it may suffer severe financial sanctions with daily fines that would affect him even more. With this, the guiding question of the research permeates How do judicial sentences related to obtaining medicines change the normal processes of access to public health in municipalities? Thus, to obtain an answer, the research will use as a universe the judicial demands in disfavor of the municipalities of Belém and Ananindeua and the form of data collection will be through consultations in the public farm court of the State of Pará, with the intention of enriching what is discussed here. through quantitative data of the lawsuits directed against these municipalities that deal with health care, in particular, the supply of medication. For this, the research will be based on two methods for the elaboration of this study. It will use characterization as a method to robustly demonstrate the issue of the judicialization of health. This time, it will use essentially bibliographical research, making up the current relevant legislation, as well as the vast doctrine that encompasses several thoughts on the subject that will be discussed and its confrontation with current jurisprudence. This means that the study will be based on the understanding of the Brazilian courts to form a better conviction on the topic addressed. And in the same way, it will base its research on the quantitative method, which through the data collected, in the period from 2019 to 2021, in 190 demands for lawsuits in disfavor of the researched entities, will demonstrate the consequences of the judicialization of health in the municipal management of the municipalities of Belém and Ananindeua, in order to achieve the general objective of this work, which is to analyze the phenomenon of the judicialization of health, in the Municipal scopes, in addition to the following specific objectives: to elaborate a timeline demonstrating the different phases related to the judicialization of health in Brazil; Discuss the changes in the management of the municipalities in question in view of the judicial sentences related to medicines; and to summarize how the phenomenon of judicialization of health in the municipalities of Belém and Ananindeua impacts those users of the public health service who only seek to be attended in an administrative way.